The impact of the Preview, Question, Read, Summary, and Test (PQRST) method on enhancing the reading comprehension skills of deaf students in the seventh grade at SLB B YRTRW Surakarta. - Chabelita Pramesti Fergiawan; Joko Yuwono; Mahardika Supratiwi (Journal of Disability, 2025)
Education plays a povital role in shaping the future of students, particulary those with special needs. Deaf students encounter challenges in language acquisition and reading comjprehension due to hearing impairments that impede their ability to process verbal information. This study investigates the impact of Preview, Question, Read, Summary, and Test (PQRST) method of enhacing the reading comprehension skills of deaf students in the seventh grade at Special School for Deaf Children Yayasan Rehabilitasi Tuna Rungu Wicara (SLB B YRTRW) in Surakarta. A pre-experimental research design employing a one-group pretest-posttest approach was employed. Nine deaf students paricipated in study, enganging in series of reading comprehension activities utilising the PQRST method. Data collection was conducted through written and oral comprehension tests before and after intervention. Statistical analysis employing the Wilcoxson Signed Rank Test was conducted to asses the method's effecteness. The findings revealed a subtansial improvement in students' reading comprehension scores following the implementation of the PQRST method. Students demonstrated enhancred capabilities in identifying main ideas, summarising texts, and answering comprehension questions. The structured approach of the PQRST method provided the systematic learning framework that supported student's cognitive processing and memory retentio. This research underscores the significance of employing structured and interactive teaching methods to optimise the learning potenstial of deaf students.